KETAKSAMAAN TIPE LEMAH UNTUK OPERATOR MAKSIMAL DI RUANG MORREY TAK HOMOGEN YANG DIPERUMUM - Sri Maryani (Universitas Jenderal Soedirman, 2012)
We discuss in this paper a weak type (p, p) inequality (where ) for maximal operator on generalized non homogeneous Morrey spaces. Our proof uses the result of Garcia-Cuerva dan Martell (2011).